It is Domestic, it Must Be Healthy: How Health Consciousness and Consumer Ethnocentrism Shape Healthiness Perception and Purchase Intentions of Domestic Food - Uzdavinyte, Elze; Aubel, Martin; Gineikienė, Justina (Organizations and Markets in Emerging Economies, 2019)
Consumer ethnocentrism (CET), healthiness perception and health consciousness have been extensively researched in regard to consumer food choices. Literature on domestic food choices provides evidence that CET positively affects consumer preferences toward domestic food. However, the effect of health consciousness on domestic food choices has not yet received a ention. Our online study (N=227, convenience sample from Lithuanian population) closes this gap by showing that health consciousness is an important individual trait in domestic food choices beyond consumer ethnocentrism and represents the first study to analyze CET in light of food healthiness perception. All constructs were measured using established self-report scales. Empirical results obtained through structural equation modelling show that (1) health consciousness increases healthiness perception and willingness to buy domestic food. Moreover, (2) health consciousness is an important individual trait in domestic food choices beyond CET; (3) healthiness perception of domestic food has an impact on consumer purchase decisions; (4) CET has a positive impact on domestic food healthiness perception. The study provides managerial implications for domestic and foreign producers.